Resection of cervical extra-intraspinal neuromas through the enlarged intervertebral foramen: Results in 34 case series patients - Chang, Chuan; Che, Xiao-Ming; Zhang, Ming-Guang (Frontiers in Surgery, 2023)
Objective: The purpose of this study was to analyze the techniques used to resection cervical extra-intraspinal neuromas (also known as cervical dumbbell neuromas) through the enlarged intervertebral foramen. Methods: A total of 34 consecutive patients (19 male, 15 female) with cervical dumbbell neuromas were reviewed retrospectively between April 2008 and May 2020. Sixteen tumors were found in the intervertebral foramen of C1-C3, four in C3-C4, and 14 in C4-T1. The tumor was exposed by intermuscular dissection and removed through the enlarged intervertebral foramen without excision of any bony structures. The incision was made along the posterior border of the sternocleidomastoid muscle for the C1-C3 tumors and along the anterior border of the muscle for the C3-C4 tumors; a transverse incision was made for the C4-T1 tumors. Results: All tumors were exposed completely, with 31 being completely removed in one stage and three recurrent tumors undergoing subtotal resection because of brachial plexus nerve adhesion. The vertebral artery and spinal cord were protected. The patients who underwent total tumor resection had no recurrence on enhanced magnetic resonance imaging during follow-up, and those who underwent subtotal resection accepted radiation therapy. None of the patients developed spinal instability. Conclusions: Cervical dumbbell neuromas can be exposed and removed through the enlarged intervertebral foramen without causing spinal instability or injury to the spinal cord or vertebral artery. This operative approach can retain the integrity of the structures of spine and should be considered the ideal approach for cervical dumbbell neuromas.